The Relationship Between Stress Levels and Alcohol Abuse in Adolescents in Banjar Sala, Bangli Regency - Ni Putu Widhi Utari; Hendro Wahyudi; Kiki Rizki Fista Andriana (Jurnal Medicare, 2026)
Adolescents are an age group vulnerable to stress due to academic, social, and emotional pressures that can lead to risky behaviors such as alcohol abuse. Poorly managed stress is often a major factor in alcohol use as a negative coping mechanism. This study aims to determine the relationship between stress levels and alcohol abuse among adolescents in Banjar Sala, Bangli Regency. The study design used a quantitative descriptive correlational approach with a cross-sectional approach and involved 159 respondents selected through purposive sampling. The research instruments included the Perceived Stress Scale (PSS-10) to measure stress levels and the Alcohol Use Disorders Identification Test (AUDIT) to assess alcohol abuse. Data analysis used the Spearman Rank test with a significance level of 0.05. The results showed that most respondents had moderate stress levels (58,5%), and the highest category of alcohol abuse was risky use (36,5%). The statistical test produced a p-value = 0.000 (p < 0.05) with a correlation coefficient of r = 0.625, indicating a strong positive relationship between stress levels and alcohol abuse. These findings support that stress plays a significant role in increasing the risk of alcohol consumption in adolescents. Therefore, preventative measures are needed through mental health education, stress management training, and increased social support so that adolescents can manage stress adaptively without using alcohol as a negative coping mechanism